A novel reconfigurable control method for an aircraft with potential actuator failures. (2017) - Xu, Xinli; Jiang, Zhen; Hu, Huosheng
This paper presents a novel reconfigurable control method for an aircraft with potential actuator failures. A Variable Structure Model Reference Adaptive Control (VS-MRAC) scheme is deployed to counteract the adverse effects when the actuator failure occurs. Combined with exponential reaching law, the convergence rate is improved and the chattering is reduced. This approach ensures that the reference input value can be tracked rapidly and accurately. The safety and stability of the aircraft is much improved during the event of actuator failures. Finally, the simulation results are given to show the effectiveness and performance of the developed method.